Possibilities of reusing sugar cane straw ash in the production of alternative binders - De Moraes, João Cláudio Bassan [UNESP] (2016)
Sugar cane production is increasing in Brazil due the demand in manufacturing sugar and alcohol. During production process, several wastes are generated, such as sugar cane straw. After a burning process of this waste material, sugar cane straw ash (SCSA) is obtained, and may be used in the production of alternative binders. The aim of this paper is to assess the possibility of reuse SCSA as supplementary cementitious material in blended Portland cement mortars and as raw material in the production of alkali-activated binders. Blended Portland cement mortars were prepared using 0%, 20% and 30% of SCSA in replacement of Portland cement. For alkali-activated mortars, the activating solution is based on sodium hydroxide (NaOH) solution and different Slag/SCSA proportions in mass were assessed: 100/0, 75/25 and 50/50. Mechanical strength of mortars cured at room temperature was tested for 7 and 28 curing days. The results confirm that enhanced mechanical properties can be obtained for both alternative binders using SCSA on its composition.